Minha Casa Minha Vida, nosso crescimento: Onde fica política habitacional? - Cleandro Krause; Renato Balbim; Vicente Correia Lima Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Created in 2009 by the federal government, Minha Casa Minha Vida (MCMV) is the largest housing policy in Brazil. Since its creation, it has financed the majority of the country's social housing provision. However, we argue that MCMV operations are detached from the national housing policy framework, explicit in the National Social Housing Fund (FNHIS) and the National Housing Plan (PlanHab). In this paper we show that MCMV is not being primarily guided by the housing deficit, a crucial concern in PlanHab. Rather, our analysis suggests that MCMV responds to strategies aimed at Brazil's economic growth. Based on data from the Ministry of Cities and Caixa Econômica Federal, the main financial agent for public housing in the country, we show that the production of housing units for low-wage families is basically located in sites where land costs are lower and production of estates is easier for entrepreneurs. Additionally, comparing MCMV's production aimed at low-wage families with that aimed at middle-wage families, we find that the program is more adherent to the latters' housing demand, than to the formers' housing deficit. Moreover, we observe that MCMV shows a rather limited range of housing solutions and types, as compared to a broader range by PlanHab. Finally, we propose some simple indicators that could be useful in monitoring the production of social housing, along with suggestions for the program's revision.
Keywords: R21; R31; 330; housing provision; housing deficit; PlanHab; MCMV; FAR; FGTS